Experimental determination of the flood wave transformation and the sediment resuspension in a small regulated stream in an agricultural catchment - D. Zumr (Hydrology and Earth System Sciences, 2017)
This paper presents the methodology used for artificial flood experiments conducted in a small artificial, trained (regulated) channel on the Nučice experimental agricultural catchment (0.5 km2), central Czech Republic, and the results of the experiments. The aim was to monitor the transformation of the flood wave and the sediment transport within the channel. Two series of experiments were carried out in contrasting initial conditions: (a) in September, when the stream banks were dry, the baseflow was negligible, and the channel was fully overgrown with vegetation; and (b) in March, when the stream banks were almost water saturated, the baseflow was above the annual average, and there was no vegetation present. Within each campaign, three successive flood waves, each with an approximate volume of 17 m3 and peak flow of ca. 40 L s−1, were pumped into the upper part of the catchment drainage channel. The transformation of the flood wave and the sediment transport regime within an approximately 400 m long channel section were monitored by measuring the discharge, the turbidity, and the electrical conductivity in three profiles along the stream. On the basis of the results, it was concluded that there is a considerable amount of deposited sediment, even in the well-trained and straight channel that can be re-mobilized by small floods. Part of the recorded sediment therefore originates from the particles deposited during previous soil erosion events. The flood waves initiated in dissimilar instream conditions progressed differently – we show that the saturation of the channel banks, the stream vegetation and the actual baseflow had a strong influence on the flood transformation and the sediment regime in the channel. The sediment moves quickly in winter and early spring, but in the later part of the year the channel serves as a sediment trap and the resuspension is slower, if dense vegetation is present.